2003
DOI: 10.2337/diabetes.52.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Induces Pancreatic β-Cell Proliferation Via Transactivation of the Epidermal Growth Factor Receptor

Abstract: We previously provided evidence that glucagon-like peptide 1 (GLP-1) induces pancreatic ␤-cell growth nonadditively with glucose in a phosphatidylinositol (PI) 3-kinase-and protein kinase C -dependent manner. However, the exact mechanism by which the GLP-1 receptor (GLP-1R), a member of the G protein-coupled receptor (GPCR) superfamily, activates the PI 3-kinase signaling pathway to promote ␤-cell growth remains unknown. We hypothesized that the GLP-1R could activate PI 3-kinase and promote ␤-cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
276
4
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(303 citation statements)
references
References 50 publications
17
276
4
6
Order By: Relevance
“…We found that phosphorylation of AMPK with liraglutide was not affected by co-treatment with an adenylate cyclase inhibitor SQ 22536 and that a cell-permeable cAMP analogue pCTP-cAMP did not cause AMPK phosphorylation and had no effect on liraglutide-induced phosphorylation of AMPK. GLP-1 is also thought to activate the PI3K/Akt pathway through epidermal growth factor receptor via GLP-1 receptor activation in beta cells [14]. However, the vascular effect of liraglutide was not altered by the PI3K/Akt inhibitor LY2294002.…”
Section: Discussionmentioning
confidence: 99%
“…We found that phosphorylation of AMPK with liraglutide was not affected by co-treatment with an adenylate cyclase inhibitor SQ 22536 and that a cell-permeable cAMP analogue pCTP-cAMP did not cause AMPK phosphorylation and had no effect on liraglutide-induced phosphorylation of AMPK. GLP-1 is also thought to activate the PI3K/Akt pathway through epidermal growth factor receptor via GLP-1 receptor activation in beta cells [14]. However, the vascular effect of liraglutide was not altered by the PI3K/Akt inhibitor LY2294002.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by our group and others have shown that GLP-1, via transactivation of the EGF receptor, activates the PI-3K/PKB signalling pathway [30,39,40,48], a cascade of signal transduction that prevents apoptosis in several systems. Therefore, we aimed at investigating the implication of PKB in GLP-1 antiapoptotic action.…”
Section: Discussionmentioning
confidence: 98%
“…GLP-1 mobilises intracellular Ca 2+ [35,36] via cyclic AMP guanine nucleotide exchange factor 2 (Epac) [37], an effect that may contribute to the insulinotropic action of the peptide. Moreover, this gluco-incretin hormone increases islet mass in mouse pancreas in vivo [31,38] and causes in vitro beta cell proliferation via transactivation of the epidermal growth factor receptor and subsequent activation of the phosphatidylinositol-3 kinase (PI-3K) and protein kinase C-ζ (PKC-ζ) signalling pathway in beta-(INS-1)-cells [30,39,40]. Finally, GLP-1 has recently been shown to delay beta cell apoptosis in Zucker diabetic rats, an animal model of diabetes [38], as well as in streptozotocin-treated mice and cytokinetreated rat islets in vitro [41].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Erk also affects insulin secretion and proliferation of β-cells (Sonoda et al, 2008). Activation of the phosphatidylinositol 3 kinase (PI3K) pathway by GLP-1 has also been reported either through direct activation by the β/γ-subunits of Gs (Kerchner et al, 2004) or through an indirect pathway involving c-src-mediated transactivation of the epidermal growth factor receptor (EGFR) (Buteau et al, 2003).…”
Section: Introductionmentioning
confidence: 99%